Spatial variability of alkalinity in the waters surrounding the Dangli Island group of Langkawi, Malaysia - Rosmee, Nurul Hidayah; Tajam, Jamil; Mohd Ishak, Mohd Azlan; Saleh, Sabiha Hanim; Tan, Aileen Shau Hwai; Abd. Aziz, Khairul Naim; Ismail, Md Nizam (Faculty of Applied Sciences, 2025)
This paper presents a comprehensive assessment of the spatial distribution of alkalinity in the waters surrounding the Dangli Island group of Langkawi during the southwest monsoon. Sampling was conducted at 12 strategically positioned stations around the island, capturing data at three distinct depths—upper, middle, and bottom. The determination of Total Alkalinity (TA) was performed using an Autotitrator, with synthetic seawater employed as a reference. Alkalinity, indicative of water's capacity to neutralize acids, plays a pivotal role in influencing pH stability. The average alkalinity values for each station revealed notable variations, with Station 11 (ST11) exhibiting the highest (2201.12 µEq/kg) for the surface water, (2260.45 µEq/kg) for the middle water and (2113.7 µEq/kg) for the bottom., while ST5 recorded the lowest among the stations. Analysis of the data indicates a slight elevation in alkalinity levels at the middle (2141.10 µEq/kg) compared to the upper (1982.07 µEq/kg) and bottom depths (2038.50 µEq/kg). Two-way ANOVA results demonstrated a significant difference between sampling stations (p-value = 0.016, p < 0.05), suggesting spatial heterogeneity. Conversely, no significant differences were observed between depth levels (p > 0.05). The study also explores the intricate relationship between salinity and alkalinity, emphasizing the nuanced dynamics of this association in the context of ocean acidification. Notably, a correlation coefficient (r) of -0.06 was obtained, indicating a very weak or negligible inverse relationship between salinity and alkalinity. This observation underscores the complexity of the interplay between these variables, influenced by factors such as biological activity, carbonate system dynamics, and human activities. The findings contribute valuable insights into the spatial distribution and factors influencing alkalinity in the marine environment surrounding the Dangli Island group, offering a foundation for future research and environmental management strategies.